Análise de parâmetros cinéticos em mulheres com Síndrome da Dor Femoropatelar no gesto de subida de escada - Silva, Danilo de Oliveira [UNESP] (2015)
Patellofemoral Pain Syndrome often affects athletes and sedentary population, causing anterior knee pain that is exacerbated during functional activities such as climbing stairs. Despite its etiology remains inconclusive, it is known that problems occur in the affected lower limb alignment, resulting from changes in local, distal and proximal to the knee. The study of ground reaction and center of pressure displacement during stair climbing is hardly used for Patellofemoral Pain Syndrome analysis, however, identify and understand if there is and how these changes occur is extremely important for Patellofemoral Pain Syndrome understanding. In this context, the aim of this project was investigating kinetic dynamic patterns in women with Patellofemoral Pain Syndrome during stair climbing. 62 women were recruited to participate in the study, 31 with Patellofemoral Pain Syndrome and 31 pain free. The participants performed 5 stair ascents under an instrumented 7 steps stairs with an embedded force platform on the fourth step. Parameters related to the center of pressure and the vertical ground reaction force were extracted...